Cigarette smoking is associated with high level of ferroptosis in seminal plasma and affects semen quality - Ou, Zhanhui (Reprod Biol Endocrinol, 2020)
PURPOSE: The effects of cigarette smoking on male semen quality are controversial, and the molecular mechanisms underlying how cigarette smoking affects semen quality are not clear yet. METHODS: In this study, semen samples from 70 heavy smokers and 75 non-smokers receiving infertility treatment were included. Basic semen parameters in non-smokers and heavy smokers were evaluated. Levels of glutathione (GSH), lipid reactive oxygen species (ROS), iron and GSH-dependent peroxidase 4 (GPX4) protein level were observed in human seminal plasma and in GC-2Spd cells exposed to cigarette smoke condensate (CSC). RESULTS: Heavy smokers had significantly higher abnormalities (sperm viability and sperm progressive motility) than non-smoking counterparts. Comparing non-smokers group, GSH level was reduced in the group of heavy smokers (P < 0.05). However, the level of lipid ROS and iron were significantly increased (P < 0.05). Besides, GSH level was reduced following treatment with CSC for 24 h, while lipid ROS and iron levels were increased (P < 0.05). However, the levels were reduced after being co-cultured with Ferrostatin-1 (Fer-1) (P < 0.05). The level of GPX4 protein was reduced after being treated with CSC in 24 h, and increased after being co-cultured with Fer-1(P < 0.05). CONCLUSION: Cigarette smoking is associated with high level of ferroptosis in seminal plasma and affect semen quality.